The cAMP-response-element-binding protein interacts, but Fos protein does not interact, with the proenkephalin enhancer in rat striatum. - Konradi, C (1993)
The proenkephalin gene is a well-studied model of transcription factor-target gene interaction in the nervous system and has been proposed as a regulatory target of the protein product of the immediate-early gene c-fos. This regulatory mechanism has been proposed, in part, because the cAMP response element 2 (CRE-2) site, the key DNA regulatory element within the proenkephalin second-messenger-inducible enhancer, avidly binds AP-1 proteins, including Fos, in vitro. However, we observe a dissociation in the time course of activation of c-fos and proenkephalin mRNA in rat striatum after administration of the dopamine D2 receptor antagonist haloperidol. This result prompted us to investigate the composition of protein complexes in striatal nuclear extracts that bind to the CRE-2 site. Even though our striatal nuclear extracts had substantial basal and haloperidol-inducible AP-1-binding activities that contained Fos, we could not detect Fos in complexes bound to the CRE-2 element. Instead, as determined by antibody supershift analysis, we detect CRE-binding protein (CREB)-like proteins binding to CRE-2 in both basal and haloperidol-stimulated conditions. Finally, we show that haloperidol induces CREB protein phosphorylation in striatum.